Final answer:
To solve the equation 62x - 3 = 6 - 2x + 1x, combine like terms, add and subtract terms to isolate x, and simplify the solution.
Step-by-step explanation:
To solve the given equation, 62x - 3 = 6 - 2x + 1x:
- Combine like terms: 63x - 3 = 6 - x
- Add x to both sides: 63x + x - 3 = 6
- Combine like terms: 64x - 3 = 6
- Add 3 to both sides: 64x - 3 + 3 = 6 + 3
- Combine like terms: 64x = 9
- Divide both sides by 64: 64x / 64 = 9 / 64
- Simplify: x = 9 / 64
Therefore, the solution to the equation is x = 9 / 64.